Estimating Smallholder Farmers’ Willingness to Pay for Sustainable Irrigation Water Use in North Western Ethiopia: A Contingent Valuation Method Study in Gumara Irrigation Project - Aklok Getnet; Kassahun Tassie; Zewdu Brehanie Ayele (Advances in Agriculture)
Ethiopia is the water tower of sub-Saharan Africa countries with 12 major river basins and 22 natural and artificial lakes, which make a median of 1,557.5 m3 of water available per person per year. This study specifically was aimed to estimate smallholder farmers’ willingness to pay for sustainable irrigation water use in northwestern Ethiopia using double-bounded dichotomous choice with a follow-up of open-ended contingent valuation questions. For this study, as a source of quantitative data, a total of 288 households were selected through a systematic random sampling method. Additionally, qualitative and secondary data were collected from the focus group discussions and desk reviews, respectively. A seemingly unrelated bivariate probit model and descriptive statistics were used to estimate households’ mean and aggregate willingness to pay. The result of the study revealed that about 283 (98.26%) households were willing to pay for sustainable irrigation water use via constructing water storage, allocation, and distribution channels. Moreover, the result from seemingly unrelated bivariate probit model regression results from double-bounded dichotomous choice questions, mean, and aggregate willingness to pay were 950.7 ETB (€25.7) and 1,087,159.09 ETB (€29,382.7) per month and per year, respectively. On the other hand, the mean and aggregate willingness to pay from the open-ended questions were 926.059 ETB (€25.03) and 1,072,990.52 ETB (€28,999.74) per month and year per household, respectively. Therefore, the study suggested for the concerned body to introduce proper irrigation water pricing systems based on households’ willingness and ability to pay. And an estimate of willingness to pay provides an indication of the demand for introducing proper irrigation water use system leading to sustainable use system.